2021
DOI: 10.15694/mep.2021.000115.1
|View full text |Cite
|
Sign up to set email alerts
|

Peer feedback as a strategy to foster feedback literacy in first-year allied health students

Abstract: IntroductionDeveloping a student's capacity to provide and utilise feedback are transferable skills from classroom to employment. Feedback literacy encompasses a student's ability to recognise, understand and take action on feedback. The link between feedback literacy and peer feedback remains under investigated. The aims of this project were twofold: firstly, to evaluate first-year allied health students' behaviours and attitudes towards feedback; and secondly, to assess the capability of these students to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(79 reference statements)
0
5
1
Order By: Relevance
“…Providing quality and timely FF is challenging in higher education because of numerous factors, including heavy teaching workloads, increased student populations, and insufficient time to observe and provide feedback. 26,27 Surprisingly, PVIF did not exhibit better reflective outcomes than PVEF or FF, which is inconsistent with prior research indicating that video review in feedback or debriefing enhances reflection. 17 Nevertheless, our findings are supported by a recent study in which video review was found to be beneficial for learning, but in which video itself did not ensure success; in this case, sufficient instructional effort is required from the tutor to redirect students' focus to critical aspects for improvement.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Providing quality and timely FF is challenging in higher education because of numerous factors, including heavy teaching workloads, increased student populations, and insufficient time to observe and provide feedback. 26,27 Surprisingly, PVIF did not exhibit better reflective outcomes than PVEF or FF, which is inconsistent with prior research indicating that video review in feedback or debriefing enhances reflection. 17 Nevertheless, our findings are supported by a recent study in which video review was found to be beneficial for learning, but in which video itself did not ensure success; in this case, sufficient instructional effort is required from the tutor to redirect students' focus to critical aspects for improvement.…”
Section: Discussioncontrasting
confidence: 80%
“…In contrast, increase in reflective abilities did not reach statistical significance in the FF group, which could be due to limited feedback time, as 1 faculty tutor had to evaluate performances and provided feedback for a class of 10 students. Providing quality and timely FF is challenging in higher education because of numerous factors, including heavy teaching workloads, increased student populations, and insufficient time to observe and provide feedback 26,27…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory factor analysis revealed a three-factor structure and the Cronbach's alpha was 0.96. Tripodi et al [ 17 ], 2021 Australia Feedback Literacy and Attitudes Survey Quantitative 138 Year 1 Osteopathy students The questionnaire were developed based on the feedback literacy framework by Carless and Boud [ 10 ] and the Cronbach's alpha was 0.86. Note: Instrument titles marked with an asterisk (*) are given based on the article content as the instrument were not given a formal title in the original articles itself.…”
Section: Resultsmentioning
confidence: 99%
“…Although majority of the instruments did not develop their instruments based on the concept of feedback literacy outlined by Carless and Boud [ 10 ] the constructs within these and more recent studies converge on the use of feedback literacy in learning. They can generally be divided into assessment of students' perception of the feedback process [ 16 , 17 , [49] , [50] , [51] , 53 , 54 ] and assessment of students’ behaviours in receiving feedback [ 17 , 52 , 55 ]. Overall, the included instruments have variable constructs for different contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation